Activité insecticide de l’huile essentielle d’Allium sativum sur le pucerondu prunier Hyalopterus pruni - BECHADDAD, Chaima; El MEDDAH, Fatima (My University, 2022)
To control aphids of Hyalopteru spruni, the separate and or alternating use of pesticides is an asset to be combined with many other control measures. To this end, a study on the effect of the essential oil of the plant Allium sativum was conducted to determine the effectiveness of this product in the control of a mealy aphids of the plum tree.The essential oil obtained by steam training was tested with 5 doses (0.1%, 0.2%, 0.3%, 0.4 and 0.5%) on aphids in the adult stage. Following the observations, the mortality values of aphids exposed to the essential oil treatment were determined after 24h, 48h, 72h, 96h and 120h. The LD50 and LD90 values were then calculated. The LD50 obtained was 3.04% and for the LD90 the value of 8.99% was recorded.
Keywords: Allium sativum; Hyalopteruspruni; biological activity.Essential oil